Vernonia polyanthes Less. (Asteraceae Bercht. & Presl), a Natural Source of Bioactive Compounds with Antibiotic Effect against Multidrug-Resistant Staphylococcus aureus - Jordana Damasceno Gitirana de Santana; Oscar Alejandro Santos-Mayorga; Jônatas Rodrigues Florencio; Mirella Chrispim Cerqueira de Oliveira; Luísa Maria Silveira de Almeida; Julianna Oliveira de Lucas Xavier; Danielle Cristina Zimmermann-Franco; Gilson Costa Macedo; Adriana Lúcia Pires Ferreira; Orlando Vieira de Sousa; Ademar Alves da Silva Filho; Maria Silvana Alves (MDPI AG, 2023)
Vernonia polyanthes is a medicinal plant used to treat many disorders, including infectious diseases. This study investigated the chemical constituents and the antibacterial activity of V. polyanthes leaf rinse extract (Vp-LRE). The chemical characterization of Vp-LRE was established using ultra-high performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UHPLC/Q-TOF-MS), and glaucolide A was identified through 1H and 13C nuclear magnetic resonance (NMR) and mass fragmentation. The cytotoxicity was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT). The antibacterial activity was assessed by minimal inhibitory concentration and minimal bactericidal concentration. Interactions between ligands and beta-lactamase were evaluated via molecular docking. UHPLC/Q-TOF-MS detected acacetin, apigenin, chrysoeriol, isorhamnetin, isorhamnetin isomer, kaempferide, 3',4'-dimethoxyluteolin, 3,7-dimethoxy-5,3',4'-trihydroxyflavone, piptocarphin A and glaucolide A. Vp-LRE (30 µg/mL) and glaucolide A (10 and 20 μg/mL) were cytotoxic against RAW 264.7 cells. Glaucolide A was not active, but Vp-LRE inhibited the Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), Escherichia coli, Salmonella Choleraesuis and Typhimurium, with a bacteriostatic effect. The compounds (glaucolide A, 3',4'-dimethoxyluteolin, acacetin and apigenin) were able to interact with beta-lactamase, mainly through hydrogen bonding, with free energy between −6.2 to −7.5 kcal/mol. These results indicate that V. polyanthes is a potential natural source of phytochemicals with a significant antibiotic effect against MRSA strains.